PENGARUH RAJIN MEMBACA BUKU TERHADAP PRESTASI SISWA DI SMA DHARMAWANGSA MEDAN - Khairani, Nur (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to analyze the influence of book-reading habits on the academic achievement of students at SMA Dharmawangsa Medan. In an increasingly evolving information era, reading books has become a crucial activity for enhancing students' knowledge and skills. The research utilized a survey method involving 150 students across various grade levels. Data were collected through questionnaires measuring reading frequency, types of books read, and academic grades obtained from school reports. Data analysis was performed using statistical techniques to identify the correlation between reading habits and learning outcomes. The results indicate that students with a high frequency of reading books achieve better academic performance compared to those who read infrequently. A significant positive correlation was found between reading frequency and academic grades, with students reading more than five books per month tending to have higher average scores. These findings suggest that consistent reading habits contribute positively to student academic growth. Consequently, it is recommended that both schools and parents actively encourage students to cultivate a reading habit to support their academic development.